Adsorption of Lead Using Pogamia Pinata Powder as A Low Cost Adsorbent - Ram, Vijay R.; Odedra, Jiva P.; Vyas, Suhas J; Tank, Savan P. (International Journal of Scientific Research in Biological Sciences, 2018)
The study on performance of low-cost adsorbent such as pinata leaves powder in the removal of Lead (II) ion from aqueous solution is performed. In present study p. piñata Leaves Powder adsorbent prepared. The adsorbent material adopted was found to be an efficient media for removal of Lead (II) ion with different parameter like Adsorbent dosages, Concentration and contact time etc. The different contact time and reduced concentration determines using Atomic Absorption Spectrophotometer (AAS). It was found that the metal uptake capacity (amount of removal) of and Lead (II) ion decreased but the adsorption capacity (percentage of removal) increased with the decrease in the concentration of and Lead (II) in the initial sample solution.